The Current State and Prospects of State financial Control Bodies Digitalization in the Russian Federation - A. I. Lukashov (Мир новой экономики, 2024)
Digitalization of state (municipal) financial control is a permanent process caused by the digital transformation of public administration. Choosing the approaches to solve this problem optimally and comprehensively is extremely important owing to the significant number of financial control bodies. The subject of the study is the activities of external and internal state (municipal) financial control bodies in terms of digitalization. The study’s goal is to develop the most effective approaches and recommendations for implementing the activities of digitalization of state (municipal) financial control bodies. The conditions and features of state (municipal) financial control bodies’ digitalization are determined. The author revealed the essence of the digitalization concept. The paper analyzed the approaches to digitalization used by the Federal Treasury and the Accounts Chamber of the Russian Federation. The analysis reveals that the Federal Treasury and the Accounts Chamber of the Russian Federation have used approaches to digitalization that are based on the use of vertically centralized and integrated approaches as well as providing of services.